Glutamate-releasing BEST1 channel is a new target for neuroprotection against ischemic stroke with wide time window - Shuai Xiong; Hui Xiao; Meng Sun; Yunjie Liu; Ling Gao; Ke Xu; Haiying Liang; Nan Jiang; Yuhui Lin; Lei Chang; Haiyin Wu; Dongya Zhu; et al. (Acta Pharmaceutica Sinica B, 2023)
Many efforts have been made to understand excitotoxicity and develop neuroprotectants for the therapy of ischemic stroke. The narrow treatment time window is still to be solved. Given that the ischemic core expanded over days, treatment with an extended time window is anticipated. Bestrophin 1 (BEST1) belongs to a bestrophin family of calcium-activated chloride channels. We revealed an increase in neuronal BEST1 expression and function within the peri-infarct from 8 to 48 h after ischemic stroke in mice. Interfering the protein expression or inhibiting the channel function of BEST1 by genetic manipulation displayed neuroprotective effects and improved motor functional deficits. Using electrophysiological recordings, we demonstrated that extrasynaptic glutamate release through BEST1 channel resulted in delayed excitotoxicity. Finally, we confirmed the therapeutic efficacy of pharmacological inhibition of BEST1 during 6–72 h post-ischemia in rodents. This delayed treatment prevented the expansion of infarct volume and the exacerbation of neurological functions. Our study identifies the glutamate-releasing BEST1 channel as a potential therapeutic target against ischemic stroke with a wide time window.